Antimicrobial Membranes Produced by Supercritical Assisted Phase Inversion - L. Baldino; S. Cardea; E. Reverchon (Chemical Engineering Transactions, 2015)
In this study, antimicrobial membranes of cellulose acetate (CA) loaded with potassium sorbate (Psb) were generated by supercritical assisted phase inversion for active packaging applications. To achieve appropriate membranes morphology, the starting solutions were prepared by dissolving Psb in water, and then, adding it to CA-Acetone solution and were processed at different pressures and temperatures. The loaded membranes were analyzed by FESEM, EDX and UV/VIS spectrophotometer, to determine: membrane morphology, distribution of the active compound inside the polymeric matrix and Psb release rate, respectively. The results indicate that, by changing the operative conditions (ranging from 150 to 250 bar, and 35 to 55 °C), cellular structures characterized by different pore size were obtained. EDX analyses showed as the active compound was uniformly distributed in the polymeric matrix at all process conditions tested. Moreover, Psb release time was influenced by membranes morphology, since the active compound diffusion was slowered when the polymer matrix was denser. These results suggest that the antimicrobial membranes, prepared in this study, could be used as food packaging material achieving a controlled release of the active compound, improving the food quality and safety.